Mempersiapkan Sumber Daya Manusia (SDM) dalam Menghadapi Tantangan Artifical Intelligence Pada Sektor Publik - Ficky Adi Kurniawan; Devi Ayu Kurniawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Artificial Intelligence (AI) is one area of technology that plays a major role in digital transformation. Human Resource Management (HRM) has an unlimited role to play in creating a fair work environment throughout the world and ensuring fairness in the company. AI analytics can be used in the human resources sector to generate strategies and solutions quickly and enable employees to align processes efficiently. The method used in this research is literature study by collecting information through articles and scientific journals. The research results show that public sector workers must acquire new skills and knowledge necessary to interact with and manage AI systems. In facing advances in AI, companies/agencies need to pay attention to HR career development through training and improving new skills and knowledge needed to interact and manage AI systems. In facing global challenges, AI must be seen as a tool, not a substitute for human resource management.